Recent Progress in Lymphangioma - Liu, Xiaowei; Cheng, Cheng; Chen, Kai; Wu, Yeming; Wu, Zhixiang (Frontiers in Pediatrics, 2021)
Lymphangioma is a common type of congenital vascular disease in children with a broad spectrum of clinical manifestations. The current classification of lymphangioma by International Society for the Study of Vascular Anomalies is largely based on the clinical manifestations and complications and is not sufficient for selection of therapeutic strategies and prognosis prediction. The clinical management and outcome of lymphangioma largely depend on the clinical classification and the location of the disease, ranging from spontaneous regression with no treatment to severe sequelae even with comprehensive treatment. Recently, rapid progression has been made towards elucidating the molecular pathology of lymphangioma and the development of treatments. Several signaling pathways have been revealed to be involved in the progression and development of lymphangioma, and specific inhibitors targeting these pathways have been investigated for clinical applications and clinical trials. Some drugs already currently in clinical use for other diseases were found to be effective for lymphangioma, although the mechanisms underlying the anti-tumor effects remain unclear. Molecular classification based on molecular pathology and investigation of the molecular mechanisms of current clinical drugs is the next step towards developing more effective individualized treatment of children with lymphangioma with reduced side effects.